Evaluation of Earthquake Victims Following the 2023 Kahramanmaras-Turkiye Earthquake: A Multicenter Trial with 8025 Cases - Karakus, Ali; Avci, Akkan; Yesiloglu, Onder; Karadag, Mehmet; Avci, Begum Seyda; Kuvvetli, Adnan; Hakimoglu, Sedat (Galenos Publ House, 2025)
Aim: Our multicenter study includes the largest number of earthquake victims reported in the literature, aiming to evaluate demographic data and outcomes of patients who presented to emergency departments following 2023 Kahramanmaras, Turkiye earthquake. Materials and Methods: Patients admitted to hospital emergency departments after the February 6, 2023 Kahramanmaras earthquakes were retrospectively evaluated over a 22-day period. Data analyzed included age, gender, triage scales, overall health status, vital signs, laboratory and imaging results, definitive diagnoses, outcomes of patients, and emergency interventions. Results: Of the 8025 patients reported in 18 centers, 51.2% (n=4112) were female, and the average age of the patients was 40.91 +/- 20.12. A total of 3578 people (57.6%) had a green triage tag, indicating good overall health with relatively minor injuries. Lower extremity fractures were the most prevalent finding in radiographs, accounting for 33.7% (n=663), of the cases, while cerebral hemorrhage, rib fractures, and lumbar fractures were the most common results in tomography scans. The three most common diagnoses were soft tissue trauma (n=1270; 21.1%), crush syndrome (n=932; 15.5%), and lower extremity fractures (n=851; 14.2%). Cast-splint application (n=813; 22.18%), central venous catheterization (n=393; 10.72%), and fasciotomy (n=322; 8.78%) were the primary procedures performed in the emergency departments. Out of the 1886 hospitalized patients, the orthopedics clinic received the highest number of admissions (n=600). A total of 3461 patients were discharged, and 495 died. Conclusion: Findings of our study revealed higher rates of morbidity and mortality than in previous earthquakes, with orthopedic injuries being the most common outcome of earthquake-related trauma. We believe that establishing tent hospitals in earthquake-prone regions and surrounding provinces, constructing long-term healthcare facilities and trauma centers with emergency services, testing facilities, imaging areas, operating rooms, hemodialysis and intensive care units, employing horizontal architecture designs, and improving referral networks can help to reduce these rates.
Keywords: Earthquake; trauma; morbidity; mortality; precautions